Type II NKT Cells: An Elusive Population With Immunoregulatory Properties - Singh, Avadhesh Kumar; Tripathi, Prabhanshu; Cardell, Susanna L. (Frontiers in Immunology, 2018)
Natural killer T (NKT) cells are unique unconventional T cells that are reactive to lipid antigens presented on the non-polymorphic major histocompatibility class (MHC) I-like molecule CD1d. They have characteristics of both innate and adaptive immune cells, and have potent immunoregulatory roles in tumor immunity, autoimmunity and infectious diseases. Based on their T cell receptor (TCR) expression, NKT cells are divided into two subsets, type I NKT cells with an invariant TCRα-chain (Vα24 in humans, Vα14 in mice) and type II NKT cells with diverse TCRs. While type I NKT cells are well-studied, knowledge about type II NKT cells is still limited, and it is to date only possible to identify subsets of this population. However, recent advances have shown that both type I and type II NKT cells play important roles in many inflammatory situations, and can sometimes regulate the functions of each other. Type II NKT cells can be both protective and pathogenic. Here, we review current knowledge on type II NKT cells and their functions in different disease settings and how these cells can influence immunological outcomes.